Formation of Ag-Fe Bimetallic Nano-Species on Mordenite Depending on the Initial Ratio of Components; Materials; Vol. 16, iss. 8 - Kotolevich Yu. Yulia; Khramov E. Evgeny; Sanchez-Lopez P. Perla; Pestryakov A. N. Aleksey Nikolaevich; Zubavichus Ya. Yan; Antunez-Garcia J. Joel; Petranovskii V. Vitalii (2023, 2023)
Title screen